Structure Elucidation and Activity of Kolossin A, the D‐/L‐Pentadecapeptide Product of a Giant Nonribosomal Peptide Synthetase1. Issue 35 (26th June 2015) - Bode, Helge B.; Brachmann, Alexander O.; Jadhav, Kirtikumar B.; Seyfarth, Lydia; Dauth, Christina; Fuchs, Sebastian W.; Kaiser, Marcel; Waterfield, Nick R.; Sack, Holger; Heinemann, Stefan H.; Arndt, Hans‐Dieter
Abstract The largest continuous bacterial nonribosomal peptide synthetase discovered so far is described. It consists of 15 consecutive modules arising from an uninterrupted, fully functional gene in the entomopathogenic bacterium Photorhabdus luminescens. The identification of its cryptic biosynthesis product was achieved by using a combination of genome analysis, promoter exchange, isotopic labeling experiments, and total synthesis of a focused collection of peptide candidates. Although it belongs to the growing class of D‐/ L‐peptide natural products, the encoded metabolite kolossin A was found to be largely devoid of antibiotic activity and is likely involved in interspecies communication. A stereoisomer of this peculiar natural product displayed high activity against Trypanosoma brucei rhodesiense, a recalcitrant parasite that causes the deadly disease African sleeping sickness.